2005
DOI: 10.1051/0004-6361:20052911
|View full text |Cite
|
Sign up to set email alerts
|

Structure in the motions of the fastest halo stars

Abstract: Abstract. We analyzed the catalog published by Beers et al. (2000, ApJ, 119, 2866 of 2106 non-kinematically selected metal poor stars in the solar neighborhood, with the goal of quantifying the amount of substructure in the motions of the fastest halo stars. We computed the two-point velocity correlation function for a subsample of halo stars within 1-2 kpc of the Sun, and found statistical evidence of substructure with a similar amplitude to that predicted by high resolution CDM simulations. The signal is due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 37 publications
0
37
1
Order By: Relevance
“…By comparing the observed distribution of stars in the L z − L ⊥ space with Monte Carlo simulations of smooth, non rotating stellar halos, the over-density found at (L z , L ⊥ ) (1000, 2000) kpc km s −1 was shown to be significant and was interpreted as evidence of an accreted stream, known as the "Helmi stream" after this discovery. Other studies have subsequently confirmed the presence of this overdensity in the L z − L ⊥ space, confirming its extra-galactic nature (Chiba & Beers 2000;Re Fiorentin et al 2005;Dettbarn et al 2007;Kepley et al 2007;Klement et al 2009;Smith et al 2009;Re Fiorentin et al 2015) and concluding that approximately 5% of the local stellar halo should be made of stars belonging to this stream. Apart from the Helmi stream, possible others have potentially been detected in the L z − L ⊥ plane (see, for example Kepley et al 2007;Smith et al 2009;Re Fiorentin et al 2015).…”
Section: On the L ⊥ -L Z Spacementioning
confidence: 62%
See 1 more Smart Citation
“…By comparing the observed distribution of stars in the L z − L ⊥ space with Monte Carlo simulations of smooth, non rotating stellar halos, the over-density found at (L z , L ⊥ ) (1000, 2000) kpc km s −1 was shown to be significant and was interpreted as evidence of an accreted stream, known as the "Helmi stream" after this discovery. Other studies have subsequently confirmed the presence of this overdensity in the L z − L ⊥ space, confirming its extra-galactic nature (Chiba & Beers 2000;Re Fiorentin et al 2005;Dettbarn et al 2007;Kepley et al 2007;Klement et al 2009;Smith et al 2009;Re Fiorentin et al 2015) and concluding that approximately 5% of the local stellar halo should be made of stars belonging to this stream. Apart from the Helmi stream, possible others have potentially been detected in the L z − L ⊥ plane (see, for example Kepley et al 2007;Smith et al 2009;Re Fiorentin et al 2015).…”
Section: On the L ⊥ -L Z Spacementioning
confidence: 62%
“…2-4, has been performed selecting stellar particles in restricted solar volumes (3 kpc in radius). These are the typical volumes over which the kinematic search of stellar streams has been focused until now (Helmi et al 1999;Kepley et al 2007;Morrison et al 2009;Smith et al 2009;Re Fiorentin et al 2005. In the coming years, with Gaia and spectroscopy-related surveys such GALAH, WEAVE, and 4MOST, we will have an almost complete view of stars up to ∼3 kpc from the Sun: distances, kinematics, ages and detailed abundances.…”
Section: Leaving the Solar Volume: Kinematic Detection Of Streams On mentioning
confidence: 99%
“…In particular, Klement et al (2009) already showed that the streams 'C2', 'C3' and 'S 3 ' are not only kinematically and chemically connected, but also spatially coherent, similar to a small overdensity at (R, z) ≈ (9.5, 0.8) kpc described by Juric et al (2008). Other streams with a common origin might be the RHLS and H99 groups (Re Fiorentin et al 2005), R2 and KFR08 (Klement et al 2009) and the S 3 streams from Dettbarn et al (2007) and Klement et al (2009), respectively. Furthermore, relations between halo streams and certain globular clusters have been suggested in several instances, based on their common position in the IoM-space. In particular, relations have been suggested between SKOa and the clusters NGC 5466, NGC 6934, NGC 7089/ M2 and NGC 6205/ M13 (Smith et al 2009).…”
Section: A Census On the Currently Known Halo Streamsmentioning
confidence: 73%
“…Indeed, the classical integrals of motion have been used successfully for finding tidal debris in the solar neighborhood Chiba and Beers 2000;Re Fiorentin et al 2005;Kepley et al 2007;Smith et al 2009); however, some limitations have to be considered (pointed out by Helmi et al 2006): First, the total angular momentum |L| is only strictly conserved in a spherical potential which is not the case for the Milky Way. However, this seems to be a minor point, because even for stars that move in axisymmetric flattened potentials, |L| is approximately conserved and similar to the third integral I 3 , for which no analytic expression exists (Binney and Tremaine 2008, Sect.…”
Section: Integrals Of Motion and Action-angle Variablesmentioning
confidence: 99%
See 1 more Smart Citation